Pengembangan media PBL berbantuan Canva untuk meningkatkan literasi ekosistem di sekolah dasar - Kintan Rizki Amanda; Ansori Ansori; Sukma Murni (Universitas Pendidikan Indonesia, 2026)
Ecosystem literacy is crucial for elementary school students in facing ecological challenges. Transmissive learning and teachers' limited ability to develop digital media hinder the development of higher-order thinking skills. This study developed Canva-assisted PBL media to improve ecosystem literacy in fifth-grade students at an elementary school in West Bandung Regency. This study used the Research and Development (RnD) method with the ADDIE model. A one-group pretest-posttest design was used to measure the media's effectiveness. Data were collected through validation sheets from media experts, material experts, and education practitioners. Teacher and student practicality questionnaires, PBL implementation observation sheets, and a 25-item ecosystem literacy test measured three dimensions of scientific literacy. The results showed that the media received valid categories from media experts and material experts, high practicality from teachers and students, and was proven effective in significantly improving students' ecosystem literacy. The integration of authentic PBL-based problem scenarios with Canva's investigative infographics was particularly effective in developing students' scientific inquiry competencies, especially in areas that are often difficult to cultivate through conventional learning.